The empire's exhibition aand the city's biennial : contemporary implications of world as picture - Ayvaz, İlkay Baliç. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
This thesis aims at offering a historical account of the ways of representing the world in two distinct eras, namely the liberal age and the present neoliberal system. It focuses on the emergence of two exhibitionary models: the world exhibition of late nineteenth century and the contemporary art biennial of late twentieth century. Both spectacular exhibitions in nature, these two exhibition models emerged or culminated in remarkable pinnacles of economic progress. While the world exhibition offered a representation of a world system based on empires and colonies, the number of contemporary art biennials throughout the world peaked in 1980s, in line with the shifting neoliberal world order, in which the organizing unit is the multicultural, competitive city. This study does not propose an anachronistic comparison between the two exhibition types or an art-historical perspective towards exhibition making. It derived from the idea that a parallel reading of these two exhibitionary models could provide an insightful ground to explore the representational diagrams of these two significant turning points in socio-economic reorganization. The world exhibitions were representative world pictures of recent progresses in objective science and machinery, where human activity came to be perceived and displayed as culture for the first time in a more direct manner than ever. The age of world exhibitions were the age of the world picture; this picture, one might argue, would metaphorically be represented in a painting. Meanwhile, the world picture drawn by the biennials can metaphorically be seen as contemporary art itself: a less palpable, multi-layered, fragmented, complex and ephemeral world installation where the diversity, democracy and self-reflexivity are on display to represent a totality of universal art and democratization.
Keywords: Art, Modern -- 19th century -- Exhibitions.; Art, Modern -- 20st century -- Exhibitions.